A Survey of the Aquatic Insects in Shatt Al-Arab River, Iraq - Sadek J.T. (Journal of Global Pharma Technology, 2016)
The study on survey of aquatic insects was done covering the zone of Basra city to Shatt A-Arab River, south of Iraq. The aquatic insects were collected using a plankton net method from three stations. There were varieties of aquatic insects belonging to 2 orders in the study sites. The orders of insect were Hemiptera and Coleoptera. During the study period, there is range from total of 26 to 58 individuals of aquatic insect trapped and collected in to Shatt A-Arab River from May to July 2018. Some species of aquatic insects (Berosus spinosus and Paracymus relaxus) were found significant (P<0.05) different compared with Plea leachi, Hydaticus histrio and Ochthebius kermanicus. This shows the richness and various species of aquatic insects in the study area. The quality of non-harmful habitats is most suitable for aquatic insects to reproduce under a natural ecosystem with abundant diet source.Keywords: Shatt Al-Arab River; Aquatic insects; Hemiptera; Coleoptera